PENGEMBANGAN INSTRUMEN DAN EVALUASI PEMAHAMAN PRODUK BAGI DIVISI PENJUALAN MENGGUNAKAN QUIZIZZ PADA PT. ACTiV - Bahtera Alam Wijaksono; Mohammad Fazrie; Dudi Parulian (LPPM Universitas Nusa Mandiri, 2023)
The development of the industrial revolution 4.0 make technology is improvement, because of that make so many things activities all fields become very simple, especially in companies engaged in the IT sector. Seeing these conditions need to upgrade the capabilities of new and old personnel, specifically for the sales force. By seeing this the team became very interested making an activity that could improve the quality and performance of the personnel by providing evaluation and training, which is expected in the future to be able to help in carrying out their duties. This community service aims to be able to provide good utilization for the company in the future. The team will use Quizizz an e-learning media delivery because attractive and interactive and for the research method used the Quasi Experimental Design. For the evaluating of a product and for the medium purposive sampling we are using documentation, observasion, pretest and posttest, for data used in making these questions category volume, profitability, product and other relevant measures. The final results from material carried out by the team the results quite 85% - 95% in very good category. The conclusion from this study is that e-learning using Quizizz is very effective in improving the ability, which previously got enough marks very good at the assessment and Quizizz can be used as a data bank, which can be used continuously as a media e-learning for other staff at PT. Alfa Cipta Technology Virtual (ACTiV).